Correlation Analysis of Vascular Endothelial Growth Factor Level with Clinicopathological Features and Prognosis in Patients with Diabetic Nephropathy: A Biopsy-based Study: VEGF in diabetic nephropathynephropathy - Zhang, Junlin; Zhu, Huixian; Tang, Qiong; Wu, Jing (Cellular and Molecular Biology, 2023)
Globally, Type 2 diabetes mellitus (T2DM) is one of the most prevalent chronic diseases, which poses a great potential threat to the human body. Diabetic nephropathy (DN), a very common complication in T2DM, is also the main trigger for end-stage renal disease. A thorough understanding of the pathogenesis is the key as well as the breakthrough for future diagnosis and treatment of DN. This investigation aims to provide more in-depth and accurate guidance for future follow-up research by analyzing the role of vascular endothelial growth factor (VEGF) in the kidney tissue of DN patients. Seventy-nine patients with suspected DN who underwent renal needle biopsy in our hospital from January 2015 to June 2019 were selected as the research participants. After the biopsy, 36 cases were confirmed as DN, and the other 43 were T2DM with primary glomerulonephritis. Determination of VEGF mRNA and protein expression in renal tissue employed PCR and Western blot, and the connection between VEGF mRNA level and clinical pathology (such as renal function, inflammatory factors and pathological manifestations) was discussed. The disease recurrence in DN patients was recorded through the 3-year prognostic followed up, and the related influencing factors were analyzed. In kidney tissue, VEGF mRNA level and protein expression were notably higher in DN patients than in diabetic patients (P<0.05). Pearson correlation coefficient analysis identified that VEGF mRNA and protein had a positive connection with blood urea nitrogen (BUN), serum creatinine (Scr), 24-hour urine total protein (24hUTP) and C-reactive protein (CRP) (P<0.05). Among the various clinicopathological features of DN patients, age, BMI, sex, family history, smoking, drinking, exercise habits, clinical presentations and pathological changes had no significant relationship with VEGF level (P>0.05), but the course of the disease, fasting blood glucose (FBG), glycosylated hemoglobin (HBALC) and pathological stages of nephropathy had a close connection with VEGF level (P<0.05). Prognostic follow-up revealed that VEGF mRNA was noticeably higher in patients with recurrence than in those without (P<0.05). When VEGF mRNA >5.20 in kidney tissue, the sensitivity and specificity for predicting the 3-year recurrence were 85.71% and 84.00% respectively (P<0.05). Finally, Logistic regression analysis identified the independence of FBG, HBALC and VEGF levels as the influencing factors for the prognostic recurrence of DN (P<0.05).VEGF expression in kidney tissue of DN patients is closely linked to renal function and increases as the disease progresses, which is an independent risk factor associated with the prognostic recurrence of DN, with great potential significance for future DN diagnosis and treatment.